2007
DOI: 10.1016/j.susc.2007.07.030
|View full text |Cite
|
Sign up to set email alerts
|

On the geometrical and electronic structure of an ultra-thin crystalline silica film grown on Mo(112)

Abstract: Abstract. The atomic structure of a well-ordered silica film grown on a Mo(112) single crystal substrate is discussed in detail using the experimental and theoretical results available to date. New photoelectron spectroscopy results using synchrotron radiation and ultraviolet spectroscopy data are presented. The analysis unambiguously shows that the ultra-thin silica film consists of a two-dimensional network of corner sharing [SiO 4 ] tetrahedra chemisorbed on the unreconstructed Mo(112) surface. The review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 77 publications
(124 reference statements)
6
73
0
Order By: Relevance
“…Nevertheless, the O 1s signal was used to calibrate the amount of oxygen on the (2x3) surface by comparison with the spectra of an ultra-thin silica film grown on the same Mo(112) substrate, for which the atomic structure has recently been determined [37,38] [42]. In the case of ultra-thin oxide films, additional screening by a m etal substrate underneath the film may result in lowering of the measured BE values.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the O 1s signal was used to calibrate the amount of oxygen on the (2x3) surface by comparison with the spectra of an ultra-thin silica film grown on the same Mo(112) substrate, for which the atomic structure has recently been determined [37,38] [42]. In the case of ultra-thin oxide films, additional screening by a m etal substrate underneath the film may result in lowering of the measured BE values.…”
Section: Methodsmentioning
confidence: 99%
“…Such a hexagonal prism slab, which is similar to double layer structures found in sheet silicates [12], has been proposed as a model for hydrophobic silica surfaces [29]. It was previously considered as a possible model for the silica film on Mo(112), but discarded because of disagreement with the experimental results [3]. This structure possesses a Si-O-Si linkage normal to the surface suggested by the IRAS results.…”
Section: Prl 105 146104 (2010) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…For better understanding of structureproperty relationships on silica-based materials, particularly of reduced dimensions, thin silica films grown on metal single crystal substrates are suggested as suitable model systems that allow the facile application of many ''surface science'' techniques. It has recently been shown that crystalline silica films and nanowires can be grown on Mo(112) [1][2][3][4][5]. The ultrathin film consists of a monolayer honeycomblike network of corner-sharing [SiO 4 ] tetrahedra, thus resulting in a SiO 2:5 stoichiometry of the film.…”
mentioning
confidence: 99%
See 2 more Smart Citations